2011
DOI: 10.3127/ajis.v17i1.541
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Introduction to the OTAM: Exploring Users’ Perceptions of their on-going Interaction with Adopted Technologies

Abstract: A common criticism directed at Davis ' (1986; 1989) Technology Acceptance Model relates to its failure to adequately frame the "experienced" user's ongoing adoption and exploitation of information technologies. Given the pervasive nature of technology into individual users' ongoing, everyday communication and information interactions, along with the "new adopter" becoming an increasingly rare entity, the TAM is in danger of becoming a somewhat obsolete framework for investigating user-technology interaction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 144 publications
(187 reference statements)
0
9
0
Order By: Relevance
“…The selection of technology, either synchronous or asynchronous, becomes important in the context of GVTs. When appropriate technology is not selected there is a chance of misinterpretation of the message, and misunderstanding among the team members which can increase the risk of reduced levels of trust and increased conflicts (Knight & Burn, 2011;Yigitbasioglu;. The reflections on the phenomenological accounts also suggest that technology enables the working of GVTs but the use of appropriate technology is important which enables smooth functioning of GVTs by reducing the challenge of misinterpretation and misunderstanding among team members, facilitating team members to be cognitively and emotionally driven towards performance.…”
Section: Technologymentioning
confidence: 99%
“…The selection of technology, either synchronous or asynchronous, becomes important in the context of GVTs. When appropriate technology is not selected there is a chance of misinterpretation of the message, and misunderstanding among the team members which can increase the risk of reduced levels of trust and increased conflicts (Knight & Burn, 2011;Yigitbasioglu;. The reflections on the phenomenological accounts also suggest that technology enables the working of GVTs but the use of appropriate technology is important which enables smooth functioning of GVTs by reducing the challenge of misinterpretation and misunderstanding among team members, facilitating team members to be cognitively and emotionally driven towards performance.…”
Section: Technologymentioning
confidence: 99%
“…A website's overall usefulness and user-friendliness encompasses the quality of the website (Loiacano, Watson, & Goodhue, 2007;Knight & Burn, 2011). In a study conducted in the US, it was found that websites designed poorly cost $30 million per day to corporate career portals (Maurer & Liu, 2007).…”
Section: Perceived Quality Of Website → Applicant's Attractiveness Ofmentioning
confidence: 99%
“…Web 2.0 platforms such as web blogs have opened a new avenue for communicating free thoughts to the masses in this digital age. Also, if the firm does not provide the testimonials themselves but direct the job-seekers to third party blogs to view the testimonials, it may likewise create a greater sense of authenticity and trustworthiness for the message which again follows from TAM and YPCM (Petty et al, 1987;Knight & Burn, 2011). This leads to the following hypotheses, H6a: The relationship between perceived quality and organizational attractiveness will be moderated by advertisement-source such that the effect will be higher for company-independent source as compared to that for company dependent source of advertisement.…”
Section: Moderating Effect Of Advertisement Sourcementioning
confidence: 99%
“…The questionnaires are divided into two sections namely; Section A comprise of respondents" background such as gender, age, race, income level, and their experiences in using mobile advertising, and Section B consists of the measurement items for the variables stated in the conceptual framework which consists of 33 items were developed to measure the construct and it"s dimensions. All measures used in this study were adapted from existing scales; perceived usefulness and perceived ease of use (Knight & Burn, 2011); informativenss (Chowdhury, Parvin, Weitenberner & Becker, 2006); credibility (Liu et al, 2012); irritation and behavioural intention (Unal, Erci, & Keser, 2011). Respondents responded to the items using a 5-point Likert-type scale with ""1"" = ""strongly disagree"" to ""5"" = ""strongly agree"".…”
Section: Measurement and Analysismentioning
confidence: 99%